Effect of glide path files with different metallurgy on intracanal bacterial extrusion by HyFlex electrical discharge machining file: An in vitro study - Priyanka Soni; Pragya Kumar; Sonali Taneja; Anshi Jain (Wolters Kluwer Medknow Publications, 2022)
Introduction: Glide path preparation permits predictable debridement and shaping of radicular space while reducing procedural errors like apical extrusion of debris and microorganisms which can postpone healing. The aim of this study was to comparatively evaluate the effect of glide path files with different metallurgy on apically extruded Enterococcus faecalis. Materials and Methods: Forty human mandibular bicuspids were selected, decoronated, and autoclaved. The samples were placed in a test apparatus of sterilized glass vials and inoculated with E. faecalis. The specimens were randomly allocated into four major groups (n = 10) each depending on the glide path file used - Group I with Proglider, Group II with EdgeGlidePath Files, Group III with Neoniti GPS, and Group IV without rotary glide path instruments using HyFlex electrical discharge machining (EDM). After glide path preparation, final canal preparation was done with HyFlex EDM. The apically extruded E. faecalis was counted as colony-forming unit and was converted into log values. Statistical analysis was evaluated using Kruskal-Wallis H Test and Mann-Whitney U-test using SPSS software; version 22.0 (SPSS INC., Chicago, IL, USA). Results: Group IV without glide path preparation technique showed maximum extrusion of E. faecalis in comparison to other groups (P < 0.05). Groups I and II showed a similar quantity of extruded bacteria. Group III showed significantly higher bacterial extrusion than Groups I and II. Conclusions: Glide path preparation groups showed less amount of apically extruded E. faecalis. EDGEGlidePath files showed lesser apically extruded E. faecalis in comparison to Proglider and Neoniti GPS.